2016
DOI: 10.1364/prj.4.0000b9
|View full text |Cite
|
Sign up to set email alerts
|

Generation and propagation characteristics of electromagnetic vortices in radio frequency

Abstract: Electromagnetic vortices, which describe the orbital angular momentum (OAM) carrying waves with a helical phase front, have recently attracted much interest in a radio frequency domain due to their potential applications in many diverse areas. In an OAM-based scenario, the antenna for OAM mode multiplexing/demultiplexing plays an essential role in controlling the overall system performance. In this paper, we demonstrated theoretically and experimentally an easily realized OAM antenna based on the traveling-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The transmit distance is the short slab of this design. It has the potential to radiate more multiple RF OAM beams by concentrically stacking the ring resonators [60,61]. The propagation characteristics and physical size of the antenna also can be improved by using a coaxial dielectric cavity as shown in Figure 4(d).…”
Section: Ring Resonatormentioning
confidence: 99%
See 1 more Smart Citation
“…The transmit distance is the short slab of this design. It has the potential to radiate more multiple RF OAM beams by concentrically stacking the ring resonators [60,61]. The propagation characteristics and physical size of the antenna also can be improved by using a coaxial dielectric cavity as shown in Figure 4(d).…”
Section: Ring Resonatormentioning
confidence: 99%
“…No potential conflict of interest was reported by the authors. antenna [59], and (c) multiple OAM modes antenna [60]. [116], (c) circularly polarized metasurface [117], (d) metasurface with PIN diodes [119]…”
Section: Disclosure Statementmentioning
confidence: 99%
“…In 1992, Allen et al first found the fact that the Laguerre-Gaussian (LG) light beams can carry a certain mode of orbital angular momentum (OAM) [1], and proposed that light beams with a helical phase front have the potential to benefit the relevant applications in optical manipulation. In addition, OAM modes are orthogonal to each other, making it possible to increase the channel capacity of wireless communication system without additional frequency resources [2], [3]. In the past decades, the OAM vortex beam has become an important research topic due to its excellent physical nature and the potential applications [4]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…The OAM modes of radio vortex waves from UCA were researched from a theoretical aspect [6], where factors affecting the mode distribution were analyzed. Later, generators carrying plane spiral orbital angular momentum (PS-OAM) were proposed to realize the beam control of OAM and to evolve on the shape of UCA [7]. Four-dimensional antenna arrays were designed to broaden the prospect of OAM waves [8], which realized multiple orbital angular momentum modes.…”
Section: Introductionmentioning
confidence: 99%